Staphylococcal Toxic Shock Syndrome Caused by Tampon Use - Cian McDermott; Michael Sheridan (Case Reports in Critical Care)
The authors report a case of near-fatal sepsis with multiorgan failure resulting from a Staphylococcal tampon-associated toxic shock syndrome, requiring a lengthy critical care admission. Successful treatment of this condition focuses on early identification, source control, and administration of antimicrobial agents. Intravenous immunoglobulin therapy used early may prevent widespread tissue necrosis.